The Influence of Financial Early Warning System on Insurance Company Share Prices to Indonesian Stock Exchange 2019-2022 - Imbang, Anatasya Stevani Elisabet; Mangantar, Maryam; Djemly, Woran (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine and analyze the influence of the Premium Growth Ratio, Claim Expense Ratio, Liquidity Ratio and Funds Adequacy Ratio on Insurance Company Share Prices on the Indonesia Stock Exchange in 2019-2022. The sampling method used a purposive sampling method and obtained 17 samples from 18 populations. The analysis technique used is multiple linear regression analysis. The results of this research show that partially the Premium Growth Ratio has no significant effect on Stock Prices, the Claims Expense Ratio has a negative and significant effect on Stock Prices, the Liquidity Ratio has a negative and significant effect on Stock Prices, the Funds Adequacy Ratio has a negative and significant effect on Stock Prices while simultaneously showing that the Premium Growth Ratio, Claim Expense Ratio, Liquidity Ratio and Funds Adequacy Ratio have a positive and significant effect on Share Prices.